2021
DOI: 10.1186/s13049-021-00877-3
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter emergency medical service dispatch in older trauma: time to reconsider the trigger?

Abstract: Background Helicopter Emergency Medical Services (HEMS) respond to serious trauma and medical emergencies. Geographical disparity and the regionalisation of trauma systems can complicate accurate HEMS dispatch. We sought to evaluate HEMS dispatch sensitivity in older trauma patients by analysing critical care interventions and conveyance in a well-established trauma system. Methods All trauma patients aged ≥65 years that were attended by the Air Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(20 reference statements)
2
3
0
Order By: Relevance
“…The first of these is likely to represent a higher acuity of age-related aetiology in these categories, and the latter is likely to reflect the Silver Trauma phenomenon [ 40 ]. Older age has previously been identified in UK HEMS as a potentially useful dispatch criteria [ 41 ], and our data provide support for this in a more specific and actionable way.…”
Section: Discussionsupporting
confidence: 81%
“…The first of these is likely to represent a higher acuity of age-related aetiology in these categories, and the latter is likely to reflect the Silver Trauma phenomenon [ 40 ]. Older age has previously been identified in UK HEMS as a potentially useful dispatch criteria [ 41 ], and our data provide support for this in a more specific and actionable way.…”
Section: Discussionsupporting
confidence: 81%
“…The rst of these is likely to represent a higher acuity of age-related aetiology in these categories, and the latter is likely to re ect the Silver Trauma phenomenon. [40] Older age has previously been identi ed in UK HEMS as a potentially useful dispatch criteria, [41] and our data provide support for this in a more speci c and actionable way.…”
Section: Discussionsupporting
confidence: 72%
“…Both G1 and G2 received AAM and CDs at similar rates when attended by a doctor/paramedic team. Griggs et al 40 recently showed that doctor/paramedic team involvement in older trauma patients frequently led to time-critical interventions, particularly prehospital anesthesia and intubation, even among patients with low-energy trauma who did not fulfill the initial criteria for immediate dispatch. This supports our finding that physicians on scene perform advanced interventions also at high age, although likely from a careful selection of cases.…”
Section: Discussionmentioning
confidence: 99%